Upravlenie trenirovocnym processom zenscin v skorostno-silovych vidach legkoj atletiki - Vrublevskij, E. P. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The purpose of this paper was to develop the recommendations for the training macrocycle construction of female athletes', specializing in speed-power kinds of track and field athletics. The results of the research allow to draw the basic conclusion that it is necessary to define such rational form of training process, where each of its characteristics mainly defining the qualitative and quantitative measure of the influence of training load on an athlete's organism (its contents, volume and organization) are strictly coordinated with the cyclic changes in women' organism, with the reflection in the psychological condition, the level of serviceability and the display of motor abilities in each phase of ovarian-menstrual cycle.